2015
DOI: 10.4047/jap.2015.7.6.437
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a "TED-Style" presentation on potential patients' willingness to accept dental implant therapy: a one-group, pre-test post-test study

Abstract: PURPOSEA survey was conducted to assess the impact of a TED-like educational session on participants' willingness to accept dental implant therapy.MATERIALS AND METHODSVolunteers interested in having information about dental implant therapies were recruited and asked to complete a two-part survey before and after an educational session. The initial survey elicited demographic information, self-perceived knowledge on dental implants and willingness to this kind of treatment. A "TED-style" presentation that prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…When an optimal occlusion is not achievable due to severe interarch misalignment resulting from the bone atrophy pattern where the maxillary arch is considerably narrower in comparison to the mandibular arch, a GBR approach could be considered a substitute for the buccal missing bone structure; however, this approach is not always feasible, especially when the GBR approach is compromised by patient‐related factors such as fear of additional surgery, financial limitations, medically comprised status, or high degree of bone resorption . Therefore, an edge‐to‐edge cusp relation is frequently used by dental technicians as an esthetically driven “compromise” solution (Fig C) .…”
Section: Discussionmentioning
confidence: 99%
“…When an optimal occlusion is not achievable due to severe interarch misalignment resulting from the bone atrophy pattern where the maxillary arch is considerably narrower in comparison to the mandibular arch, a GBR approach could be considered a substitute for the buccal missing bone structure; however, this approach is not always feasible, especially when the GBR approach is compromised by patient‐related factors such as fear of additional surgery, financial limitations, medically comprised status, or high degree of bone resorption . Therefore, an edge‐to‐edge cusp relation is frequently used by dental technicians as an esthetically driven “compromise” solution (Fig C) .…”
Section: Discussionmentioning
confidence: 99%
“…Given the nature of the pretest-posttest design of this study, the prospective data will be collected at two moments 6 .…”
Section: Data Collectionmentioning
confidence: 99%
“…28 However, there is evidence to show that when accurate information is presented appropriately, it can be helpful to patients. Ghanem and colleagues 29 undertook a study to investigate the effect of a TED-like presentation (Technology, Entertainment and Design website that provides short online talks by expert speakers) on patients' willingness to accept implant treatment. Patients who were interested in potentially undergoing implant treatment completed a questionnaire before and after the short presentation and the researchers found that respondents were significantly more likely to accept implant treatment after the information had been provided.…”
Section: The Patient Experiencementioning
confidence: 99%
“…Patients who were interested in potentially undergoing implant treatment completed a questionnaire before and after the short presentation and the researchers found that respondents were significantly more likely to accept implant treatment after the information had been provided. 29 These findings highlight the importance of the profession providing and collating high quality information in different formats and ensuring that it is readily accessible. It is also important that patients are asked how they would like information to be provided 30 and the advent of individualised provision of care means that patients' views should be considered when providing this information.…”
Section: The Patient Experiencementioning
confidence: 99%